Pharmacologic antagonism of dopamine receptor D3 attenuates neurodegeneration and motor impairment in a mouse model of Parkinson's disease. (February 2017) - Elgueta, Daniela; Aymerich, María S.; Contreras, Francisco; Montoya, Andro; Celorrio, Marta; Rojo-Bustamante, Estefanía; Riquelme, Eduardo; González, Hugo; Vásquez, Mónica; Franco, Rafael; Pacheco, Rodrigo
Abstract: Neuroinflammation involves the activation of glial cells, which is associated to the progression of neurodegeneration in Parkinson's disease. Recently, we and other researchers demonstrated that dopamine receptor D3 (D3R)-deficient mice are completely refractory to neuroinflammation and consequent neurodegeneration associated to the acute intoxication with 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). In this study we examined the therapeutic potential and underlying mechanism of a D3R-selective antagonist, PG01037, in mice intoxicated with a chronic regime of administration of MPTP and probenecid (MPTPp). Biodistribution analysis indicated that intraperitoneally administered PG01037 crosses the blood-brain barrier and reaches the highest concentration in the brain 40 min after the injection. Furthermore, the drug was preferentially distributed to the brain in comparison to the plasma. Treatment of MPTPp-intoxicated mice with PG01037 (30 mg/kg, administrated twice a week for five weeks) attenuated the loss of dopaminergic neurons in the substantia nigra pars compacta, as evaluated by stereological analysis, and the loss of striatal dopaminergic terminals, as determined by densitometric analyses of tyrosine hydroxylase and dopamine transporter immunoreactivities. Accordingly, the treatment resulted in significant improvement of motor performance of injured animals. Interestingly, the therapeutic dose of PG01037 exacerbated astrogliosis and resulted in increased ramification density of microglial cells in the striatum of MPTPp-intoxicated mice. Further analyses suggested that D3R expressed in astrocytes favours a beneficial astrogliosis with anti-inflammatory consequences on microglia. Our findings indicate that D3R-antagonism exerts a therapeutic effect in parkinsonian animals by reducing the loss of dopaminergic neurons in the nigrostriatal pathway, alleviating motor impairments and modifying the pro-inflammatory phenotype of glial cells. Highlights: Systemic D3R-antagonism attenuates nigrostriatal neurodegeneration induced by MPTP. Inhibition of D3R-signaling favours activation of astrocytes with anti-inflammatory properties. D3R-antagonism reduces the motor impairment in a mouse model of Parkinson's disease. D3R-antagonism attenuates the acquisition of activated-morphology by microglia.